Posicionamiento de la empresa Agromat S. A. de la parroquia "Febres Cordero" en el periodo 2021 - Enríquez Becilla, Erick Fernando (2022)
This case study is being carried out with the purpose of identifying the poor management of commercial strategies in the company AGROMAT S.A. resulting in low customer traffic. Through the investigation that will be carried out in the company AGROMAT S.A., it will be possible to obtain a conglomerate of factors that allow to be evaluated, so that, in such a way, the company takes the corresponding decisions for the commercial and economic performance of the organization, leading to be a more profitable and competitive business in the local market. The main objective is to determine the positioning of the company AGROMAT S.A. in the period 2021 in the Babahoyo canton. This research work is directed by the research line, called: Information and communication systems, entrepreneurship and innovation of the Commerce career. It has a mixed research methodology that allowed obtaining the results from which finally the conclusions and recommendations were obtained.